Genesis of the Problem of Historiosophic Preparation of the Future Teacher - Galyna Gamrets’ka (Pedagogical Discourse, 2013)
The influence of social and political factors onto the formation of the essence and functional abilities of historiosophic preparation of the future teacher at different stages of Ukrainian society’s development in the XXth century has been examined in the article. The attention is concentrated on the necessity of taking into account experience of the previous decades that is essential condition of realization of tasks of historiosophic preparation of the teacher of modern national school. The topicality for the modern conditions of person-oriented approach in teaching historic material, which were reflected in educational programs, textbooks and methodological approaches during the times of national-democratic revolution, has been determined. The conclusion about the necessity of methodological reorientation of historiosophic component in the content of pedagogical education, which must favor formation of the teacher of new world outlook and moral culture, has been done.